2013
DOI: 10.1021/cg400652b
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Deficient Oxide Growth by Subliming the Oxide Source Material: The Cause of Silicide Formation in Rare Earth Oxides on Silicon

Abstract: The fundamental issue of oxygen stoichiometry in oxide thin film growth by subliming the source oxide is investigated by varying the additionally supplied oxygen during molecular beam epitaxy of RE2O3 (RE = Gd, La, Lu) thin films on Si(111). Supplying additional oxygen throughout the entire growth was found to prevent the formation of rare earth silicides observed in films grown without an oxygen source. Postgrowth vacuum annealing of oxygen stoichiometric films did not lead to silicide formation thereby confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…There are only a few studies in the oxide MBE literature using evaporation of the metal oxide from an effusion cell. [19][20][21][22][23] Vapor pressure data indicate that SnO 2 sublimes in the form of suboxides (SnO x ) with vapor pressures sufficient for reasonable flux rates at practically feasible effusion cell temperatures, i.e., ∼10 −5 Torr at 1300 • C. 24 Figure 1(b) shows RHEED during BaSnO 3 growth on (001)SrTiO 3 at a substrate temperature of 800 • C, using the SnO 2 source. The RHEED pattern is streaky from the start of the growth and remains so throughout, without any significant decrease in the intensity.…”
mentioning
confidence: 99%
“…There are only a few studies in the oxide MBE literature using evaporation of the metal oxide from an effusion cell. [19][20][21][22][23] Vapor pressure data indicate that SnO 2 sublimes in the form of suboxides (SnO x ) with vapor pressures sufficient for reasonable flux rates at practically feasible effusion cell temperatures, i.e., ∼10 −5 Torr at 1300 • C. 24 Figure 1(b) shows RHEED during BaSnO 3 growth on (001)SrTiO 3 at a substrate temperature of 800 • C, using the SnO 2 source. The RHEED pattern is streaky from the start of the growth and remains so throughout, without any significant decrease in the intensity.…”
mentioning
confidence: 99%
“…Early thermochemical experiments showed that in thermodynamic equilibrium, the heating of a mixture of Ga 2 O 3 , In 2 O 3 , and SnO 2 with their respective metals produces the sub-oxides Ga 2 O, 13 In 2 O, 14 and (SnO) n (n ¼ 1, 2, 3, and 4), 15 respectively. Volatile sub-oxides with different stoichiometries are also known to form during the thermal decomposition or sublimation of metal oxides 16 rare-earth oxides, 17,18 or during pulsed laser ablation of oxides (e.g., SnO 2 (Ref. 19…”
mentioning
confidence: 99%
“…Furthermore, additional oxygen (6N purity) was introduced in the growth chamber using a piezo leakage valve to stabilize the oxygen partial pressure during growth. The additional oxygen is used to prevent silicide formation due to the oxygen depletion of the Gd 2 O 3 source material to realize epitaxial growth of stoichiometric Gd 2 O 3 (Bierwagen et al, 2013). The oxygen supply was started shortly after the beginning of the Gd 2 O 3 growth, so that silicon surface passivation by SiO 2 formation is prevented.…”
Section: Methodsmentioning
confidence: 99%